2017
DOI: 10.18632/aging.101335
|View full text |Cite
|
Sign up to set email alerts
|

Sexually dimorphic effects of dietary sugar on lifespan, feeding and starvation resistance in Drosophila

Abstract: Lifespan and health in older age are strongly influenced by diet. Feeding Drosophila melanogaster diets high in sugar has increasingly been used as an experimental model to understand the physiological effects of unhealthy, contemporary human diets. Several metabolic parameters and physiological responses to nutrition are known to be dependent on the sex of the animal. However, sexual dimorphism in the responses to high-sugar diets in fruit flies has not been examined. Here we show that a high-sugar diet in Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 32 publications
9
22
0
Order By: Relevance
“…Drosophila melanogaster has been used as a model for nutritional physiology studies for many years (Piper, 2017;Rauser, Mueller, & Rose, 2004;Tatar, Post, & Yu, 2014), and their requirements for development and female reproduction are well studied (Begg & Robertson, 1950;Consuegra et al, 2019;Piper, 2017;Sang & King, 1961). We also know that the lifespan of male and female adults respond differently to dietary interventions and that the sexes show different preference in macronutrient balance (Bowman & Tatar, 2016;Camus, Huang, Reuter, & Fowler, 2018;Chandegra, Tang, Chi, & Alic, 2017;Lee, Kim, & Min, 2013;Magwere, Chapman, & Partridge, 2004;Regan et al, 2016;Wu et al, 2020), but no one has systematically determined the minimal requirements of each nutrient class for adult lifespan and whether these requirements differ between the sexes. Defining these limits is important since it is fundamental to understanding how adult-specific diet interventions, such as DR and DB, may be operating to modify lifespan.…”
Section: Introductionmentioning
confidence: 99%
“…Drosophila melanogaster has been used as a model for nutritional physiology studies for many years (Piper, 2017;Rauser, Mueller, & Rose, 2004;Tatar, Post, & Yu, 2014), and their requirements for development and female reproduction are well studied (Begg & Robertson, 1950;Consuegra et al, 2019;Piper, 2017;Sang & King, 1961). We also know that the lifespan of male and female adults respond differently to dietary interventions and that the sexes show different preference in macronutrient balance (Bowman & Tatar, 2016;Camus, Huang, Reuter, & Fowler, 2018;Chandegra, Tang, Chi, & Alic, 2017;Lee, Kim, & Min, 2013;Magwere, Chapman, & Partridge, 2004;Regan et al, 2016;Wu et al, 2020), but no one has systematically determined the minimal requirements of each nutrient class for adult lifespan and whether these requirements differ between the sexes. Defining these limits is important since it is fundamental to understanding how adult-specific diet interventions, such as DR and DB, may be operating to modify lifespan.…”
Section: Introductionmentioning
confidence: 99%
“…rescues Spen-KD adult lifespans. Unlike the high-protein diet, excess carbohydrates is 564 beneficial and confers starvation resistance in mated females, and to a lesser extent 565 males (Chandegra et al 2017). As described in our previous study, Spen-KD alters 566 carbohydrate metabolism and changes glycolytic flux (Hazegh et al 2017).…”
Section: Diet Composition Is a Primary Variable In The Metabolome At mentioning
confidence: 71%
“…We see in 567 the adult stage wherein HSD is a more favorable diet composition for longevity of Spen-568 KD mated females than do CTRL-KD. This is not conserved in males, which is not 569 entirely surprising given the significantly smaller benefit of increased sugar conferred to 570 adult males in general (Chandegra et al 2017). HSD alters the metabolite profiles of 571…”
Section: Diet Composition Is a Primary Variable In The Metabolome At mentioning
confidence: 99%
“…Although we found no sexual dimorphism in the pattern of VT041723-GAL4 expression in the brain (data not shown), a closer look at the expression of sex-specific fru and dsx in VT041723-GAL4 neurons would provide further insight into possible mechanisms underlying sexual dimorphism. In addition, sexspecific differences in feeding responses to salt (Walker et al, 2015), yeast (Ribeiro and Dickson, 2010), amino acids (Ganguly et al, 2017) and sugars (Chandegra et al, 2017) have been reported. Given the possibility of functional connectivity between VT041723-GAL4 neurons and peripheral taste neurons, it will be of interest to determine whether specific gustatory input is involved in sexdependent variation in the proboscis holding phenotype.…”
Section: Discussionmentioning
confidence: 99%